Using educational robotics to teach fundamental feedback control concepts - Avgousti, Sotiris; Christoforou, Eftychios G.; Masouras, Panicos; Vourkos, Eleftherios; Panayides, Andreas S. (My University, 2025)
This work examines the role of educational robotics towards teaching high-school children basic automatic control concepts including feedback, the structure and the differences between open- and closed-loop control systems, the basic elements of a closed-loop system, the effect of external disturbances, the tracking error, as well as practical issues concerning control hardware implemen tation. The ideas are exemplified with hands-on exercises and experiences from a STEM summer school based on educational robotics.
Robotics in Education
Keywords: Educational robotics; Educational Robot Design and Programming